Dose-dependent effects of biochar amendment on early rice seedling growth and nursery substrate properties in Southern China - Chen, Liming; Ao, Jiahong; Gao, Zihong; Xu, Ziyi; Yu, Hanxuan; Zhang, Haixuan; Yu, Changjie; Wei, Linshan; Li, Shaochen (Frontiers in Agronomy, 2025)
IntroductionBiochar regulates rice growth and development as well as improves soil quality, and shows application potential for early rice seedling cultivation in double-cropping rice systems in South China.MethodsThis study applied biochar at rates of 0%, 10%, 20%, 30%, 40%, and 50% of total nursery soil volume to systematically evaluate its impacts on early rice seedling agronomic traits, root architecture, nutrient uptake, and soil physicochemical properties.Results and DiscussionThe results demonstrate that that the biochar application rate had a significant dose-dependent effect on rice seedling growth indicators. The 30% treatment showed the best overall performance, with seedling leaf length (increased by 42.1% compared to the 0% treatment), plant height, dry matter accumulation, SPAD value, and leaf area (increased by 54.6%) all being significantly higher than those in other treatments. Concurrently, this treatment achieved the highest values for root length (increased by 18.6%), root volume, and number of root tips, along with a significant 58.8% increase in potassium content within the root zone. The 20% and 30% treatments significantly promoted stem base width (increased by 12.7%–18.0%) and the strong seedling index (increased by 84.6%). Conversely, the 40% and 50% treatments had inhibitory effects, resulting in significant reductions in seedling leaf length, stem base width (decreased by 24.9%), dry weight, and leaf area. Root fresh weight also decreased by 11.9%–17.1%. Biochar application significantly enhanced substrate water-holding capacity, reduced bulk density, and increased total porosity (by 23.0%) and organic matter content. Notably, the 40% and 50% treatments caused a dramatic increase in available potassium levels within the substrate (increasing by 29.7 times), accompanied by abnormally significant elevations in pH and EC. Correlation analysis further revealed that the strong seedling index was highly significantly positively correlated with leaf area and seedling sturdiness, while being highly significantly negatively correlated with the root-shoot ratio. In conclusion, a 30% biochar application rate was identified as the optimal dosage, synergistically enhancing early rice seedling morphological development, root system growth, and the soil microenvironment.